Coalition of Violence Claims Against Journalists in Detik.Com and Floresa 2021-2025 - Gita Pratiwi; Hanny Hafiar; Pandan Yudapramesti (Jurnal Komunikasi, 2026)
Violence against journalists in Indonesia is a recurring democratic issue, but news coverage often frames it as isolated incidents rather than structural problems. Previous studies have focused on legal protection, victim experiences, or case classification without systematically mapping how actors and claims form discourse coalitions across different media arenas. Using Discourse Network Analysis (DNA), we coded 391 actor statements from Detik.com (mainstream national) and Floresa.co (local alternative media) for six claim types (individual misconduct, procedural response, systemic violence, institutional accountability, justice demands, and obstacles to journalistic work) based on framing and discourse coalition theory. Network visualization was performed using DNA software and Gephi. The Indonesian National Police (Polri) dominated Detik.com (91 statements) with an individual-perpetrator to systemic claim ratio of 4.9:1. Floresa.co showed stronger advocacy actor presence (AJI, KKJ, LBH Pers, AMSI) and a near-balanced ratio (9:7). Two main coalitions emerged: individual-perpetrator-procedural and systemic-structural. Mainstream media reproduces institutional-procedural storylines, while alternative media enables systemic-structural advocacy coalitions, but discourse institutionalization of systemic claims remains incomplete in national public spheres. Protecting journalists requires not only legal reform but also transforming news routines that systematically prioritize institutional narratives over advocacy perspectives.